When Does an Increase in a Firm’s Operational Effectiveness Reduce its Economic Performance? - Lee, Minjae (Academy of Management Proceedings, 2023)
Conventional wisdom suggests that an increase in a firm’s operational effectiveness will increase its economic performance. However, we show that an increase in a firm’s operational effectiveness can decrease its economic performance. Specifically, a firm’s increase in operational effectiveness of its existing projects following a positive demand shock can limit its profitable growth as its strategic resources are not allocated to pursuing new projects, thereby incurring opportunity costs that can lower its economic performance. We corroborate this reasoning in the context of the liquefied natural gas industry, which experienced a positive demand shock in 2000 due to energy market liberalization. We find empirically that a firm’s operational effectiveness increases its Tobin’s Q in the pre-shock period and reduces it in the post-shock period.
Keywords: AOM Annual Meeting Proceedings 2023; AOM Boston 2023; Strategic Management; dept.mgt